1970
DOI: 10.1111/j.1399-3054.1970.tb06479.x
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Growth and Flowering and Increase in Content of Endogenous Gibberellins in Gladiolus Plants Treated with the Growth Retardant CCC

Abstract: A|)plicati()ii of tbe growlb retardant CGC to gladiohis i)lants resulted in stimulalion of stem lengtb, increased number of flowers per sjjikc and a slight advancement of antbesis date. Leaves of treated jilants were bcavier tban control and contained a bigber amount of water and cbloropliyll. The antbocyaniii content in petals was also greatly increased. CCC had little or no effect on the content of the endogenous gibberellins in the acidic ethyl acetate fraction, bvit markedly increased tbe content of the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

1970
1970
1986
1986

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 21 publications
1
10
0
2
Order By: Relevance
“…But also if this growth substance activity would be more auxin-like, or if an auxinlike activity would be of additional influence, the observation remains that the mesocotyl effect of these fractions is enhanced by the presence of CCC in the medium. This latter observation seems to confirm the results of VAN BRAGT (1969), HALEVY & WITTWER (1965) and HALEVY & SHILO (1970). Yet experimental data are always too few to permit a synthetic view of the mode of action of CCC, GA and endogenous growth substances in the process of flower formation in Wedgwood iris.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…But also if this growth substance activity would be more auxin-like, or if an auxinlike activity would be of additional influence, the observation remains that the mesocotyl effect of these fractions is enhanced by the presence of CCC in the medium. This latter observation seems to confirm the results of VAN BRAGT (1969), HALEVY & WITTWER (1965) and HALEVY & SHILO (1970). Yet experimental data are always too few to permit a synthetic view of the mode of action of CCC, GA and endogenous growth substances in the process of flower formation in Wedgwood iris.…”
Section: Discussionsupporting
confidence: 88%
“…Five days after application of CCC the total gibberellin content of the plants, as determined with the dwarf pea assay, was slightly larger than that of the controls. HALEVY & SHILO (1970) observed that application of CCC to gladiolus plants caused an increased growth and a greater number of flowers. The content of endogenous gibberellins in the aqueous fraction of their extract had also increased.…”
Section: Introductionmentioning
confidence: 98%
“…The application of CCC to the apices under conditions which encourage fiower abortion produced results similar to those obtained from the GA treatment (Table 1), Despite the common assumption that CCC inhibits gibberellin biosynthesis and reduces its level in the tissue (Cross 1968, Lang 1970, several cases are known where this growth regulator had no effect on GA level or even increased the GA content (Van Bragt 1969, Halevy and Shilo 1970, Rodriguez-Pereira 1970, Reid and Crozier 1972, Erydman and Wareing 1974. A similar effect of reduced "blindness" by CCC treatment was obtained in gladiolus (Halevy and Shilo 1970). In roses there was no decrease in GA level due to CCC treatment (Zieslin and Halevy 1976d).…”
Section: Discussionmentioning
confidence: 54%
“…Standards were replicated five times. The method used was as described earlier (12,15). Incubation at 25 C on the rotator (1 rpm) lasted 32 hr.…”
mentioning
confidence: 99%